Use Of Traditional Medicine In Non Insulin-Dependent Diabetes Mellitus - Valdivia, Freddy (1996)
Objectives: To assess the use and wont of traditional medicine by patients with non insulin - dependent diabetes mellitus (NIDDM), in the Department of Endocrinology of the National Guillermo Almenara Irigoyen Hospital (NGAIH).Methods: A test to 102 patients that attended the ambulatory consulting room of Endocrinology of the NGAIH, between May and Jun of 1996, was performed.Results: 68.6% of patients used some traditional medicine method, with no difference between sex. Gentianella arborocea, Uncaria sp. And Cyclanthera pedata were among the most used. 73% of the patients used 2 or more drugs, and 60% obtained a favourable effect. The use of traditional medicine was not related with diet, tablets or insulin therapy.Conclusions: The use of traditional medicine by patients with NIDDM is frequent. This use is unknown by the physician, and although the favourable effect of these drugs has not been scientifically demonstrated, patients use a great diversity of them. It is necessary to perform more studies to demonstrate the utility of these drugs for treatment of NIDDM.